Proses Pembelajaran Ekstrakurikuler Paduan Suara Menggunakan Metode Vokalisi - Dadang Dwi Septiyan; Haura Dwitayu Bachri; Syamsul Rizal (Program Studi Pendidikan Musik FBS UNP, 2025)
Purpose: This research aims to analyze and describe the learning process and vocalization methods used. The problems studied are the learning process of vocalization in Smanda Choir and the analysis of vocalization methods in Smanda Choir. This research approach refers to the concept of vocalization and the choir itself with the support of other relevant concepts. Methods: The research method uses a qualitative method with descriptive explanation. Data sources come from observation, interviews, documentation studies, and relevant literature studies in providing a comprehensive perspective. Result and Discussion: The results of this study indicate that the vocalization method has several steps that must be taken, but in Smanda Choir SMAN 2 Kota Serang there are findings that the vocalization method used is divided into four steps, namely, breathing, mumbling, intonation intervals (arpeggio) and vocal formation. This is based on the reference order with the provisions set by the trainer. The main contribution of this study lies in the identification and documentation of the vocalization method structure specifically adapted by the Smanda Choir coach-an area that has not been widely explored in previous studies. This research also offers a contextual perspective on how the vocalization method is adjusted based on its effectiveness for students within the setting of a secondary school extracurricular program. Conclusion: This study can be concluded that the vocalization method in Smanda Choir has a process and order that is tailored to the needs based on the techniques and methods developed, while the researcher analyzes the method based on what the trainer does with the selection of vocalization method points according to the needs and procedures that are adjusted based on the effectiveness of the students.